Energy consumption and spatial diversity trade-off in autonomic Wireless Sensor Networks: The (m,k)-Gur Game approach - Semprebom, Tiago; Pinto, A. R. [UNESP]; Montez, Carlos; Vasques, Francisco (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In some Wireless Sensor Network (WSN) applications, it may be necessary to keep a large number of nodes sensing and transmitting data to a base station in order to have unbiased measurement values. Therefore, in addition to the traditional energy consumption issues, the spatial diversity of the monitored area is another relevant metric to evaluate the performance of a WSN. Nevertheless there is a clear trade-off between these two parameters, as keeping the sensors active all the time will deplete the nodes batteries and therefore will shorten the network lifetime. Fortunately, for the case of some applications it is possible to specify as a Quality of Service (QoS) parameter the number of periodically expected messages in the base station. Therefore, it will be possible to balance QoS against energy consumption. This paper proposes an approach called (m,k)-Gur Game that aims a trade-off between the expected QoS and the spatial coverage diversity. Simulation results show the effectiveness of the proposed approach. © 2013 IEEE.